Youth in Colombia in view of generational transfer and income generation in the forage based livestock sector - Activity Report - Triana Ángel, Natalia; Burkart, Stefan (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
Alquería, a major dairy company in Colombia, leads one of the most important rural education initiatives in the country, aimed specifically at the livestock sector (dairy farmers), their families, and new generations of young milk producers: Heirs of Tradition. After years of pilot training programs, field days, and technical training sessions, the company identified low schooling rates in milk producing areas as a key element hindering productivity, product quality, and overall continuity of new generations in the livestock industry (Triana & Ariza, 2019). The objective of Heirs of Tradition, a project operating since 2012 to the present, is that young generations of milk farmers from different, even conflict-affected regions of Colombia can be effectively trained in livestock practices at no cost, thus enhancing their knowledge and skills on subjects such as soil management, animal care, and environmental sustainability.